2017
DOI: 10.1002/ijc.30715
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the IGF‐IRS pathway are associated with outcome in mCRC patients enrolled in the FIRE‐3 trial

Abstract: The Insulin-like growth factor (IGF)/IGF-receptor pathway with its scaffolding proteins Insulin Receptor Substrate (IRS)1 and IRS2 are crucial regulators of metabolism and progression in metastatic colorectal cancer (mCRC). The goal of the study was the identification of predictive and prognostic markers among IRS1, IRS2, IGF1 and IGF-1R SNPs in mCRC patients enrolled in the FIRE-3 trial. Four SNPs of IRS (IRS1 rs1801278, rs1801123; IRS2 rs1805097, rs2289046) and 4 SNPs of IGF1-IGFR1 (rs6214, rs6220, rs2946834… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…A recent report on patients with colorectal cancer treated with chemotherapy together with EGFR or VEGF inhibitor revealed that overactivation of the IGF1R also constitutes a poor prognostic factor, particularly in patients bearing RAS wild-type tumors. 62 These findings echo prior observations that high expression of IGF1R (though without proof of its activation) is a poor prognostic biomarker in gastric 63 and breast cancer. 1 In conclusion, excessive antiautophagic signaling via IGF1R has a major negative effect on anticancer immunosurveillance, thus reducing patient prognosis.…”
Section: Discussionsupporting
confidence: 81%
“…A recent report on patients with colorectal cancer treated with chemotherapy together with EGFR or VEGF inhibitor revealed that overactivation of the IGF1R also constitutes a poor prognostic factor, particularly in patients bearing RAS wild-type tumors. 62 These findings echo prior observations that high expression of IGF1R (though without proof of its activation) is a poor prognostic biomarker in gastric 63 and breast cancer. 1 In conclusion, excessive antiautophagic signaling via IGF1R has a major negative effect on anticancer immunosurveillance, thus reducing patient prognosis.…”
Section: Discussionsupporting
confidence: 81%
“…IRS1 is a scaffolding protein that activates and regulates downstream cell-signaling pathways such as PI3K/Akt, leading to metabolic activity, including glucose uptake and protein synthesis, and decreased apoptosis. This pathway is a main signaling cascade in controlling the cellular process promoting carcinogenesis 11,38 . IRS1 and a single member of the Akt family, Akt2, are important signaling molecules related to a diabetic phenotype such as IR; at the genomic level, each is amplified in various cancers, including CRC 11,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is a main signaling cascade in controlling the cellular process promoting carcinogenesis 11,38 . IRS1 and a single member of the Akt family, Akt2, are important signaling molecules related to a diabetic phenotype such as IR; at the genomic level, each is amplified in various cancers, including CRC 11,39,40 . The IRS1 and AKT2 genes are thus key components of this pathway, but studies of the association of their genetic variants with CRC have been limited and conflicted 11,14,[40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations